2000
DOI: 10.1128/jvi.74.18.8648-8657.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Duck Hepatitis B Virus Reverse Transcriptase in Cells Is Nonencapsidated and Is Bound to a Cytoplasmic Structure

Abstract: The hepadnavirus reverse transcriptase binds cotranslationally to the viral pregenomic RNA. This ribonucleoprotein complex is then encapsidated into nascent viral core particles, where the reverse transcriptase copies the viral RNA into DNA. Here we report that 75% of the duck hepatitis B virus reverse transcriptase present in transfected LMH cells does not follow this well-known pathway but rather exists in the cell separate from the core protein or nucleocapsids. The nonencapsidated reverse transcriptase is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
5
37
0
Order By: Relevance
“…For the host cell, the Hε-independent HP transferase activity could contribute to cellular alterations. It has been reported that unpackaged HP or DP can accumulate in cells replicating HBV or DHBV (78)(79)(80) and could have DNA synthesis activity in the absence of its cognate ε RNA (42; this report). Also, DP can initiate DNA synthesis not only in cis (i.e., using itself as the primer) but also in trans, using multiple fragments derived from DP (34,44), and both DP (43,44) and HP (this report) can initiate DNA synthesis from sites other than the authentic Y residue in their respective TP domains (cryptic site priming).…”
Section: Figmentioning
confidence: 99%
“…For the host cell, the Hε-independent HP transferase activity could contribute to cellular alterations. It has been reported that unpackaged HP or DP can accumulate in cells replicating HBV or DHBV (78)(79)(80) and could have DNA synthesis activity in the absence of its cognate ε RNA (42; this report). Also, DP can initiate DNA synthesis not only in cis (i.e., using itself as the primer) but also in trans, using multiple fragments derived from DP (34,44), and both DP (43,44) and HP (this report) can initiate DNA synthesis from sites other than the authentic Y residue in their respective TP domains (cryptic site priming).…”
Section: Figmentioning
confidence: 99%
“…To begin a structural assessment of DHBV P, we raised six immunoglobulin G monoclonal antibodies (MAbs) against the DHBV P terminal protein domain (amino acids 1 to 207) (43) and determined the exposure of their epitopes to in vitrotranslated P by immunoprecipitation. In vitro-translated P primes DNA synthesis in the presence of dGTP and ε (40) and hence is an excellent source of properly folded, enzymatically active P that is not buried within capsids.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerase inside the capsids cannot reach the substrate once part of the replicating RNA or DNA template is exposed irreversibly to the capsid exterior and becomes nuclease sensitive. It has also been reported that nonencapsidated DHBV polymerase is enzymatically inactive (56).…”
Section: Discussionmentioning
confidence: 99%